Retaining employment in the hospital setting: A descriptive phenomenological study of Indonesian nurses’ experiences - Utari Christya Wardhani; Rr. Tutik Sri Hariyati (Belitung Raya Foundation, Indonesia, 2023)
Background: Losing competent nurses due to turnover can have adverse effects on healthcare administration, service delivery, and organizational dynamics. Frequent staff turnover can hinder optimal nursing practices, but some nurses remain committed. Therefore, understanding factors that foster sustained engagement and retention is crucial to create a retention strategy. Objective: This study aimed to explore the current experience of Indonesian nurses who retain their jobs in the hospital setting. Methods: A phenomenological design was employed in this study, with ten nurses selected using purposive sampling. Semi-structured interviews were used to gather data from a private hospital in Batam, Indonesia, between January and March 2022. A conventional content analysis was used to analyze the data. Results: The participants had an average total work experience of 10.4 years and an average age of 35.6 years, ranging from 28 to 44 years. The majority of the participants were females, held bachelor’s degrees, and were married. Three main themes were developed in this study: solid teamwork, adequate compensation, and professional career development. Conclusion: Retaining experienced nurses in hospitals is influenced by antecedents such as teamwork, pay, and career growth. These findings offer nursing and hospital managers insights into developing policies and strategies to improve hospital nursing retention programs in Indonesia and beyond.